A comprehensive review of carbon anode materials for potassium-ion batteries based on specific optimization strategies. Issue 9 (11th April 2023) - Yuan, Fei; Li, Yanan; Zhang, Di; Li, Zhaojin; Wang, Huan; Wang, Bo; Wu, Yusheng; Wu, Yimin A.
Abstract : This review mainly focuses on the discussion of mechanisms behind improved potassium storage properties, starting from some specific optimization strategies, and presents a perspective for the further development of carbon anodes. Abstract : Carbonaceous materials have been regarded as promising anodes for potassium-ion batteries (PIBs) due to their low cost and good conductivity. However, the larger size of K + will unavoidably cause the electrode structure to collapse upon repeated insertion/extraction, and meanwhile encounters slow diffusion kinetics, thus resulting in fast capacity decay and poor rate. To solve these issues, heteroatom-doping and pore-structure engineering have been proved to be effective in increasing defects, expanding the interlayer spacing, accelerating ion migration, and accommodating volume fluctuation, etc ., and as a result the capacity, rate, and cyclability are greatly improved. Besides, electrolyte/binder optimization and electrode composition design are conducive to forming a stable and uniform solid electrolyte interphase layer, which favors ion diffusion and interfacial stability, thereby leading to enhanced rate and cyclability. Despite this, a systematic conclusion on the effect of these optimization strategies on potassium storage is still lacking, and has rarely been reported so far. Hence, this work mainly focuses on the discussion of the mechanism behind the improved potassium storage properties, starting from the structure–performance relationship based on the abovementioned strategies. The perspectives on development of carbon anodes to enable their further application in PIBs are also provided.